Analisis Dampak Berbagi Pengetahuan Implisit dan Eksplisit terhadap Kinerja Karyawan di Industri Garmen - Bramantiyo Eko Putro; Rahmat Ramdani (Program Studi Teknik Industri Universitas Setia Budi, 2021)
Eastern Modern Apparel (EMA) is a textile company located in Cipeuyeum, Cianjur Regency. This research was conducted to determine the impact of knowledge sharing on the performance of employees of PT. EMA. Several divisions in PT. EMA makes knowledge sharing among individuals still lacking so that knowledge of employee performance improvement is not fully evenly distributed. The model used is a development of the Theory of Planned Behavior with the addition of several factors. These factors are expected relationships, expected contributions, pleasure in helping others, self-competence, availability of resources, technology, trust, attitudes toward sharing, intention to share and by adding some factors to sharing explicit knowledge and sharing implicit knowledge. Data collection was carried out by distributing questionnaires directly or online. The data obtained is used to test the conceptual model emipirically using structural equation modeling. The conceptual model was tested with 220 samples. The results showed that the availability of resources, attitudes towards sharing, intention to share knowledge had a positive impact on explicit knowledge sharing activities. Sharing explicit and tacit knowledge has a positive impact on employee performance with a coefficient value of 0,001 but not significant. Keywords: knowledge sharing, employee performance, SEM, textile industry